The Influence of Biologic Width on Altered Passive Eruption Treatment - Vidya Nursolihati; Marie Louisa (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Altered passive eruption (APE) is a condition in which the relationship between teeth, alveolar bone, and soft tissues creates an excessive display of gingiva, generally known as a gummy smile. Coslet classified APE into four case types, based on the gingival and osseous relationships. The treatment options can be determined based on its classification and considering the concept of biologic width. Case: This case report presents two cases of APE type 1A. The first case is a 36‑year‑old, systemically healthy, non‑smoking female with a complaint of gummy smile after orthodontic treatment five years ago. The second case is a 19‑year‑old, systemically healthy, non‑smoking female with a complaint of short teeth and uneven gingival margins. Case Treatment: The first case was treated with a combination of soft and hard tissue crown lengthening, while the second case was treated with only soft tissue crown lengthening. Discussion: Various crown lengthening techniques must be carried out without disturbing the biologic width. In the first case, although based on the examination it was classified as APE type 1A with gingivectomy treatment, there was a change in the gingival margin position so the distance to the crest of the alveolar bone was < 3 mm. Therefore, flap elevation and ostectomy were performed. Conclusion: In treating APE, biologic width is one of the most important factors to be considered, along with the amount of attached gingiva and the distance of the alveolar crest to the CEJ. Maintaining biologic width is crucial for gingival health and stable treatment outcomes.